Uterine Leiomyoma with Intravenous Leiomyomatosis - Murphy, M; Kothari, A; Westaby, S; Kehoe, S; Handa, A (2005)
Uterine fibroids are occasionally complicated by intravenous leiomyomatosis that may spread to involve the heart. We present the successful management of such a case which was originally diagnosed as a deep venous thrombosis (DVT) in association with a uterine fibroid. © 2004 Elsevier Ltd. All rights reserved.